2022
DOI: 10.1002/srin.202200212
|View full text |Cite
|
Sign up to set email alerts
|

Modification Mechanism of Lanthanum on Alumina Inclusions in a Nonoriented Electrical Steel

Abstract: The modification mechanism of lanthanum on alumina inclusions in a nonoriented electrical steel at 1600 °C is investigated using laboratory experiments. Inclusions are analyzed using an automatic scanning electron microscope equipped with energy‐dispersive spectrum at 1, 5, 10, and 30 min after lanthanum treatment. The contents of total oxygen (TO), total sulfur (TS), and total lanthanum (TLa) in steel are analyzed. Results show that Al2O3 inclusions are modified by lanthanum in two ways. One is that the disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…An interesting approach to control the inclusion shape by rare earth (RE) elements was described by Luyckx et al, [17] and results show that RE elements positively affect the globular sulfide formation and mechanical properties of sulfur-containing steel. Much work so far has focused on the metallurgy role of RE elements in steel, and RE elements can contribute to inclusion modification [9,[18][19][20][21][22][23][24][25][26][27][28] and microstructure refinement [22,[29][30][31][32] in steel. Wang et al [23] reported that the inclusion shape changed from cluster to spherical and spindle shapes with a round surface when Ce was added to Al-killed IF steel.…”
mentioning
confidence: 99%
“…An interesting approach to control the inclusion shape by rare earth (RE) elements was described by Luyckx et al, [17] and results show that RE elements positively affect the globular sulfide formation and mechanical properties of sulfur-containing steel. Much work so far has focused on the metallurgy role of RE elements in steel, and RE elements can contribute to inclusion modification [9,[18][19][20][21][22][23][24][25][26][27][28] and microstructure refinement [22,[29][30][31][32] in steel. Wang et al [23] reported that the inclusion shape changed from cluster to spherical and spindle shapes with a round surface when Ce was added to Al-killed IF steel.…”
mentioning
confidence: 99%